Determination of Trace Chromium(VI) with 3-Methoxy-Azomethine H in Surface-Active Agents - Chen, Wen-Bin; Wang, Hai; Du, Yu-ling (Asian Journal of Chemistry, 2013)
In the presence of microemulsion cetyltrimethyl ammonium bromide and CH3COOH-CH3COONa buffer at pH 6.2, the condition of colour reaction of chromium(VI) with 3-methoxy-azomethine H was studied and a new spectrophotometric method for the determination of micro chromium(VI) has been established. Results showed that in the presence of CH3COOH-CH3COONa, the maximum absorption wavelength and apparent molar absorptivity are 480 nm and 8.5 × 104 L mol-1 cm-1, respectively. Beer’s law is obeyed in the range of 0.08-15.0 μg for chromium(VI) in 10 mL solution. The detection limit is 0.02 μg/10 mL. The recovery was 102.3-103.8 %. The method has been applied to the determination of trace chromium(VI) in natural water and the result was in accordance with that of the standard spectrometry method.